New approaches to regional economic history. Economic growth, wealth and distribution of production factors in nineteenth-century Argentina (Quinto Sol, 2012)
This paper presents this section, composed by three texts, by M. F. Barcos, T. Guzman and J. L. Martiren
Keywords: wealth; distribution; productive factors; Argentina